(untitled) (Comunicação & Inovação, 2021)
Amid the COVID-19 pandemic, access to reliable sources of information is becoming increasingly necessary to keep us updated on the latest news about the disease. At an already worrying and stressful time, we analyze in this article the sharing of internet memes as a tool, not only for exposing values ​​and opinions, but also for reinforcing stereotypes and prejudices, which can contribute to an increase and the emergence of new tensions and hate speech. Through a joint analysis of authors such as Bakhtin, Bosi, Lippman and Lotman, we establish a discussion about the communicational and ideological processes present in the sharing and production of these messages, and we observe some of the effects that content of this type can have on society, such as spread of prejudice and attacks on the Chinese people and their descendants.